The views and experiences of HIV research participants in sub-Saharan Africa: a worked example of a qualitative systematic review - Nalubega, Sylivia; Evans, Catrin (HIV Nursing, 2014)
HIV clinical trials are increasingly being conducted in sub-Saharan Africa [1–3]. There is a tension between the pressure to increase levels of research participation whilst at the same time ensuring informed consent and the protection of participants’ rights [4,5]. Researchers need to be aware of the particular ethical issues that underpin HIV research conducted in lowincome settings. This necessitates hearing from those who have agreed to participate in research and who have experienced the research process.This qualitative systematic review aims to synthesise existing qualitative literature to answer the question: What are the views and experiences of HIV research participants in sub-Saharan Africa? The review aims to highlight key issues that need to be addressed to ensure high-quality ethical HIV research practice in sub-Saharan Africa.